Does Public Debt Affect Economic Growth? An Empirical Investigation Of Upper-Middle-Income Countries - Nita Viviani Nurhanifah; Romi Bhakti Hartarto; Diah Setyawati Dewanti (Universitas Udayana, 2025)
Public debt has increased dramatically over the past few decades. The emergence of budget crisesin developing countries has led to this phenomenon. Using panel data from 2013 to 2022, thisstudy investigates the impact of public debt on economic growth in 11 upper-middle-incomecountries. The panel data regression model was estimated using the fixed effect model. The findingsshow that public debt has a significant and positive impact on economic growth. Therefore, thegovernment must cut back on public debt procurement, implement structural reforms, andestablish a credible regulatory framework to ensure long-term economic growth and debtsustainability.